Assessment of power quality indices over a decade of control in Argentinian distribution system - Issouribehere, Pedro (2010)
The electricity distribution service in the Buenos Aires metropolitan area of Argentina, which was privatized in the early nineties, is carried out by three different Utilities and the control is performed by a Regulatory Agency (ENRE). By the time this control began, the existing limits in IEC standards for Power Quality were adopted in order to obtain a starting point for the local regulation. In addition, the equipment employed to perform the measurements also meets IEC standards. The aspects of Power Quality which are regulated, and therefore controlled, are voltage magnitude, voltage disturbances - harmonic distortion and flicker - , and long-term interruptions - 3 minutes or longer duration -. In every site in which the limits established for Power Quality are exceeded, the Utility is penalized. The aim of the article is to show the results obtained over more than 10 years of permanent control. The carried out studies mainly consisted of processing the data collected since the beginning of the control in order to obtain: disturbance trends over the years, comparisons of the levels measured in different Utilities as well as disturbance behaviors throughout the day. In addition to this, the degree of fulfillment achieved by the Utilities is also assessed.